2009
DOI: 10.1007/s11270-009-0249-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Deep Groundwater Quality in Kathmandu Valley Using Multivariate Statistical Techniques

Abstract: This study was carried out to assess the overall water quality and identify major variables affecting the deep groundwater quality in Kathmandu Valley, Nepal. Forty-two deep wells were sampled during premonsoon and monsoon seasons in 2007 and analyzed for the major physicochemical variables. The water quality variables such as NH 4 + -N, Fe, Pb, As, and Cd at most of the sampling locations exceeded the World Health Organization guideline levels for drinking water. Multivariate statistical techniques such as fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 16 publications
3
36
0
1
Order By: Relevance
“…Additionally, contribution of anthropogenic metal contaminations is reluctant in the studied timeseries in the groundwater wells. These findings are consistent with the results of previous study which pointed out seasonal variability has no significant effect on deep groundwater quality [17]. The similar studies also indicated no seasonal variability of arsenic in the groundwater [15] [16].…”
Section: Temporal (Seasonal) Variation Of Arsenicsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, contribution of anthropogenic metal contaminations is reluctant in the studied timeseries in the groundwater wells. These findings are consistent with the results of previous study which pointed out seasonal variability has no significant effect on deep groundwater quality [17]. The similar studies also indicated no seasonal variability of arsenic in the groundwater [15] [16].…”
Section: Temporal (Seasonal) Variation Of Arsenicsupporting
confidence: 93%
“…A study reported negative ORP value up to −195 mV in deep groundwater [14]. Likewise, another study indicated low ORP value in deep groundwater with mean value of −82 mV in pre monsoon and −56 mV in monsoon [17]. The groundwater wells in the study area are relatively anoxic, as indicated by low ORP values.…”
Section: Physicochemical Parameters and Metalsmentioning
confidence: 62%
“…Most of the groundwater wells of group (B) with high mineralization are located in CGWD, whereas many groundwater wells of group (A) with low mineralization are located in the NGWD and SGWD (Figure 10). Chapagain et al [19] also reported similar result in the groundwater of the valley, indicating that the high mineralization in the CGWD. The high mineralization in the CGWD may be attributed to geochemical heterogeneity of the sediment in groundwater districts of the Kathmandu Valley where there is a presence of finer particles and trace elements in the sediments of central part of the valley [43].…”
Section: Cluster Analysismentioning
confidence: 59%
“…Most of the water quality parameters examined were not normally distributed except temperature. Therefore, Spearman's rank correlation coefficient was applied as a non-parametric measure of correlation between the monitored variables [19] [27]. Kaiser-Meyer-Olkin (KMO) and Bartlett's test were employed to examine the suitability of data for PCA.…”
Section: Statistical Treatment Of Data and Multivariate Analysismentioning
confidence: 99%
“…As a result there is an immense pressure on groundwater resources in the valley. The ground water is depleting due to over extraction and surface water catchments are becoming degraded (ADB/KUKL, 2010 (Khatiwada et al 2002;Maharjan et al 2006;Chapagain et al 2009;Shrestha et al 2010;Chapagain et al 2010 (CBS, 2008). The precipitation is dominated by monsoon rainfall, which lasts for the months of July to September and contributes 80% of annual precipitation (JICA, 1990).…”
Section: Introductionmentioning
confidence: 99%